Evolution of antiviral treatment chronic for hepatitis B, C and D - K. V. Zhdanov; K. V. Kozlov; V. S. Sukachev (Журнал инфектологии)
In the review is presented evolution of sights on treatment of patients with chronic hepatitises since 70-th years of XX century to the present days. Stages of development of therapy sick of chronic hepatitises В, С and D are consistently characterised. The basic emphasis is made on acurrent state of a problem and the prospects opening before researchers. Algorithms of treatment of patients with chronichepatitises are presented.